THE ROLE OF CLINICAL LEADERSHIP AND WORK ENGAGEMENT IN IMPROVING PATIENT SAFETY CULTURE: INTERPROFESSIONAL COLLABORATION MEDIATOR AT EMHAKA HOSPITAL - Meilyana Maria Isabela Kwary; Rokiah Kusumapradja; Erry Yudhya Mulyani (CV. Bunda Ratu, 2025)
This study is motivated by the importance of building an effective patient safety culture in the hospital environment, which can be influenced by factors such as clinical leadership and work engagement. This study aims to analyze the effect of Clinical Leadership and Work Engagement on patient safety culture mediated by Interprofessional Collaboration of nurses at Emhaka Hospital. The research design used was quantitative with a cross-sectional approach. The study sample consisted of 118 nurses selected using purposive sampling techniques and calculated using saturated side. Data were collected through a 4-point Likert scale questionnaire, which included the variables of Clinical Leadership, Work Engagement, Interprofessional Collaboration, and Patient Safety Culture. Data analysis was performed using SEMP-PLS (Structural Equation Modeling Partial Least Squares) software. The results showed that Clinical Leadership and Work Engagement had a significant effect on Patient Safety Culture, both directly and through the mediation of Interprofessional Collaboration. These findings emphasize the importance of improving clinical leadership and nurse involvement in improving interprofessional collaboration, which in turn can strengthen patient safety culture at Emhaka Hospital. This study contributes to the development of hospital policies that focus on improving patient safety through effective leadership and increasing nurse work engagement. Keywords: Clinical Leadership, Work Engagement, Patient Safety Culture, Interprofessional Collaboration